MicroRNA-132-3p alleviates neuron apoptosis and impairments of learning and memory abilities in Alzheimer's disease by downregulation of HNRNPU stabilized BACE1. Issue 21 (2nd November 2021) - Qu, Jie; Xiong, Xiaowei; Hujie, Gulibaha; Ren, Jun; Yan, Lihui; Ma, Liqun
ABSTRACT: Alzheimer's disease (AD) is a progressive neuro-degenerative disease characterized by dementia. MicroRNAs (miRNAs) are involved in many diseases, including AD. MiR-132-3p has been identified to be downregulated in AD. In this study, we explored the effects of miR-132-3p on neuron apoptosis and impairments of learning and memory abilities. Aβ1-42-stimulated SH-SY5Y cells were used as in vitro models of AD. An AD-like homocysteine (Hcy) rat model was established to evaluate the effects of miR-132-3p on AD pathogenesis in vivo . RIP, RNA pull down and luciferase reporter assays were conducted to investigate the relationship between miR-132-3p and its downstream target genes. The viability and apoptosis of SH-SY5Y cells were measured by CCK-8 and TUNEL assays. The rat spatial learning and memory abilities were accessed using Morris water maze test. Results indicated that miR-132-3p was downregulated in SH-SY5Y cells after Aβ1-42 treatment and promoted cell apoptosis. Mechanistically, miR-132-3p targeted heterogeneous nuclear ribonucleoprotein U (HNRNPU). HNRNPU acted as an RNA binding protein (RBP) to regulate the mRNA stability of β-site amyloid precursor protein cleaving enzyme 1 (BACE1). Overexpression of HNRNPU or BACE1 reversed the effects of miR-132-3p overexpression on the viability and apoptosis of Aβ1-42-treated SH-SY5Y cells. In vivo experiments revealed the downregulation of miR-132-3p in the hippocampus of Hcy-treated rats. MiR-132-3p suppressed levels of apoptotic genes in hippocampus and reduced impairments of learning and memory abilities in Hcy-treated rats. In conclusion, miR-132-3p reduces apoptosis of SH-SY5Y cells and alleviates impairments of learning and memory abilities in AD rats by modulating the HNRNPU/BACE1 axis.